Copper-Catalyzed Synthesis of Fused Imidazopyrazine N-Oxide Skeletons - Taşdemir, Volkan; Kuzu, Burak; Tan, Meltem; Genç, Hasan; Menges, Nurettin (Synlett, 2019)
N-Propargyl-2-aroylimidazoles synthesized and converted into the corresponding ketoximes. Under various conditions, several mono- and diketoxime imidazole derivatives were formed by converting the carbonyl or carbonyl and propargyl groups into oxime groups. N-Propargyl monooxime imidazole derivatives were cyclized by treatment with CuI to give various imidazopyrazine N-oxides. Several copper salts, such as CuOAc, CuSO4, and CuOTf, formed the same cyclization product. This cyclization reaction occurred only in the presence of Cu(I) or Cu(II) salts; other transition metals such as Au, Ag, In, and Fe did not yield cyclic products. The nucleus-independent chemical shift method was used to calculate the aromaticity of the bicyclic rings.
Keywords: alkynes; cyclization; copper catalysis; imidazopyrazine oxides; oximes